Some Problems in the Study of Oceanic Religion - Keesing, Roger M. (Anthropologica, 2022)
The author notes that certain 19th-century ideas persist in the anthropological study of religion. Using the concepts of "mana" and "tapu" the author demonstrates the tenaciousness of early reifications grounded more in Western preoccupations than in Polynesian modes of thought, following lines suggested by Rodney Needham's critique of the notion of "soul substance" in Needham's paper, "Skulls and Causality" (1977).